Correction: Reactions of metallodrugs with proteins: selective binding of phosphane-based platinum(ii) dichlorides to horse heart cytochrome c probed by ESI MS coupled to enzymatic cleavage. Issue 5 (3rd May 2018) - Mügge, Carolin; Michelucci, Elena; Boscaro, Francesca; Gabbiani, Chiara; Messori, Luigi; Weigand, Wolfgang
Abstract : Correction for 'Reactions of metallodrugs with proteins: selective binding of phosphane-based platinum(ii ) dichlorides to horse heart cytochrome c probed by ESI MS coupled to enzymatic cleavage' by Carolin Mügge et al., Metallomics, 2011, 3, 987–990.